Identification of sperm morphometric subpopulations in cooled‐stored canine sperm and its relation with sperm DNA integrity. (20th February 2017) - Urbano, M; Ortiz, I; Dorado, J; Hidalgo, M
Contents: The aims of this study were to (i) identify different morphometric subpopulations in cooled‐stored canine sperm and their patterns of distribution during cool‐storage for up to 240 hr and (ii) determine whether or not morphometric sperm subpopulations (sP) are related to sperm DNA integrity. For that purpose, morphometric parameters were analysed by computer‐assisted sperm analysis (CASA) and sperm DNA fragmentation (sDFi) using the sperm Halomax test. Four morphometric sperm heads subpopulations were identified: sP1 (large and rounded), sP2 (large and elongated), sP3 (small and rounded) and sP4 (small and elongated). sP1 was the most predominant subpopulation for up to 72 hr and thereafter sP3 increased progressively. sDFi increased after 48 hr of cool‐storage. Although sP3 showed a positive correlation with sDFi, and both increased over time, it could not be ensured that only the sperm with fragmented DNA are accumulated in sP3. In conclusion, sP3 and DNA fragmentation increased progressively during cool‐storage, becoming possible indicators of sperm damage. However, it cannot be concluded that sP3 only contains sperm with fragmented DNA.